Crustacean prey in the diet of fishes from deep waters of the Eastern Ionian Sea. (3rd January 2018) - Anastasopoulou, Aikaterini; Mytilineou, Chryssi; Smith, Christopher J.; Papadopoulou, Konstantia N.
Abstract : The gut analysis of 26 fish species caught in the deep waters of the Eastern Ionian Sea showed that crustaceans were a substantial resource for fish found in deep- water environments, comprising 37 crustacean taxa. Among all species examined, 77% included crustaceans in their guts. Dendrobranchiata/Caridea shrimps were the most frequent crustacean prey found in the guts of almost all examined fishes, with high values of relative abundance (N%). Season (summer, autumn) and fish behaviour (demersal, benthic) were not found to affect the diet of the examined fish species. Galeus melastomus could be considered to be a separate case showing the most diverse diet comprising all the crustacean groups. Differences in the proportion of the main crustacean categories consumed by the examined fish species were observed. The low richness and preference towards specific crustacean taxa or different crustacean species could be considered as an indication of interspecific competition for the same food resource in the oligotrophic waters of the Eastern Mediterranean. The occurrence of different crustacean taxa in the gut of some species through the analysed seasons, could be related to differences in prey availability or to selective preference for certain prey which in turn could be linked to different energetic requirements for growth and reproduction of predators.